Ultra-lightweight polyimide fiber prepreg, method for preparing the same, and composite material
Patent Information
- Application Number
- CN202310759135.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-06-26
AI Technical Summary
[0009]为了克服现有技术存在的不足,本发明的目的在于提供一种超轻聚酰亚胺预浸料的制备方法,其能够解决现有预浸料制备工艺中聚酰亚胺丝束无法均匀展平的问题
[0032](1)可以实现超轻聚酰亚胺纤维预浸料的生产;
Smart Images

Figure CN116790009B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials, and more particularly to polyimide fiber prepregs, their preparation methods, and composite materials. Background Technology
[0002] In recent years, with the iterative upgrading of modern industries such as new spacecraft, national defense and military industry, marine industry, automobile manufacturing, new energy and sports equipment, there is an urgent need for materials with high specific strength, high specific modulus, corrosion resistance, high temperature resistance, impact resistance, fracture resistance, fatigue resistance and high strength and lightweight. This undoubtedly provides a broad application market and development potential for high-performance fiber reinforced resin matrix composites.
[0003] High-performance fiber-reinforced resin matrix composites are structural materials with two or more phases. While maintaining their basic physical and chemical properties, each phase contributes to composite materials with unparalleled performance advantages, meeting the practical needs of industrial development. Currently, mainstream reinforcing fibers include carbon fiber, glass fiber, aramid fiber (PPTA), poly(p-phenylenebenzodioxazole) fiber (PBO), and ultra-high molecular weight polyethylene fiber (UHMWPE). However, the inherent performance defects of these fibers limit the application areas and lifespan of their composites. For example, in humid environments, the polar amide groups on the PPTA fiber molecular chain have strong hydrophilicity (water absorption up to 7.75%), thus affecting the mechanical properties and dimensional stability of the prepared composite material. Under light irradiation, the oxazole rings in the PBO fiber molecular chain are highly sensitive to ultraviolet light. Prolonged irradiation causes the oxazole rings to break, forming unstable amide bonds, which then decompose into small monomers. This severely limits the usability of PBO fibers. Furthermore, PBO fibers have low surface activity, are smooth, and exhibit poor interfacial adhesion to the resin matrix, further hindering the reinforcing and toughening effects of the fiber reinforcement in resin-based composites. UHMWPE fibers have a melting temperature of approximately 136℃ and a glass transition temperature of approximately 95℃. At higher temperatures (140℃), the tensile strength decreases by 16.84% after 1 hour of use. The —CH2—CH2— structure of the molecular chain makes the fiber surface inert, resulting in poor interfacial adhesion to the resin matrix, further limiting the application temperature and range of this type of composite material.
[0004] High-performance polyimide (PI) fibers are a class of cyclic-chain type high-performance fibers containing imide ring structures in their molecular backbone. They possess excellent comprehensive properties, including high strength and modulus (tensile strength up to 4.5 GPa, initial modulus up to 201 GPa), high temperature resistance (initial decomposition temperature > 420℃), low temperature resistance (not brittle at -269℃), solvent resistance, UV radiation resistance, flame retardancy and self-extinguishing properties, high dimensional stability, high electrical insulation, low dielectric constant, low creep, and low vacuum volatility. In extreme environments (aerospace, deep-sea operations, disaster relief, national defense, etc.), they offer significant advantages over other high-performance fibers and can be used as reinforcements in high-performance fiber-reinforced resin matrix composites. They hold promise as a replacement for other high-performance fibers, improving the application areas, lifespan, and material performance reliability of resin matrix composites.
[0005] In existing technologies, most polyimide fiber-reinforced polyimide resin composite materials and their preparation methods utilize polyimide fiber fabrics to reinforce thermosetting polyimide resins. These methods require the preparation of prepregs through thermal drying to remove solvents and a cyclization process, followed by hot pressing to produce the polyimide fiber-reinforced thermosetting polyimide resin composite material. This material exhibits excellent comprehensive performance characteristics, with a glass transition temperature as high as 350℃, an interlaminar shear strength reaching 40MPa, and a dielectric constant as low as 3.21.
[0006] Chinese patent application CN201410366226.3 discloses a polyimide fiber prepreg, its preparation method, and its application. The polyimide fiber prepreg comprises 40-80% by weight of polyimide fiber and 20-60% by weight of resin. The polyimide fiber prepreg provided by this invention is a prepreg prepared by impregnating polyimide long fibers or their fabrics as reinforcing fibers with cyanate ester resin, epoxy resin, bismaleimide, or benzoxazine resin, etc.
[0007] Chinese patent application CN201910656740.3 discloses a method for preparing polyimide prepreg, characterized in that the method includes: (1) processing a thermoplastic polyimide resin solution to obtain a resin film; (2) subjecting the resin film to hot rolling treatment with polyimide fibers to obtain polyimide prepreg.
[0008] The preparation methods for polyimide fiber prepregs disclosed in the two patent documents are basically similar, both including a coating process and a hot-pressing roller lamination process, and the resin content is controlled between 20% and 60%. However, currently, neither of the aforementioned patent documents discloses any technology related to ultralight polyimide fiber prepregs, meaning that ultralight polyimide fiber prepregs cannot be produced. Furthermore, the existing two-step prepreg production process for polyimide fibers has the problem of failing to achieve uniform flattening of the polyimide filaments. Summary of the Invention
[0009] In order to overcome the shortcomings of the existing technology, the purpose of this invention is to provide a method for preparing ultralight polyimide prepreg, which can solve the problem that polyimide filaments cannot be uniformly flattened in the existing prepreg preparation process.
[0010] Another object of the present invention is to provide an ultralight polyimide prepreg, wherein the unit area mass of the ultralight polyimide prepreg can reach 80 g / m². 2 the following.
[0011] Another object of the present invention is to provide a composite material comprising an ultralight polyimide prepreg.
[0012] According to the purpose of this invention, a first aspect of the invention provides a method for preparing an ultralight polyimide prepreg, comprising the following steps:
[0013] 1) The resin is coated to obtain a resin film;
[0014] 2) The polyimide fibers are processed sequentially as follows: unwinding, sizing, flattening, and drying;
[0015] 3) The polyimide fiber obtained in step 2) is combined with the resin film obtained in step 1) by hot pressing and rolling to obtain polyimide prepreg.
[0016] The preparation method of this invention can improve the production efficiency and capacity of polyimide fiber prepregs, while reducing production costs and improving the performance of polyimide fiber prepregs. Specifically, previously, sizing required separate sizing of polyimide fibers before they could be used to produce prepregs, while this patent directly combines the sizing step and the prepreg compounding step consecutively, saving sizing time and reducing labor and material waste costs.
[0017] Preferably, in step 1), the resin is a thermoplastic or thermosetting resin. Thermoplastic resins include, but are not limited to, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polymethyl methacrylate, polyester, polyoxymethylene, polyamide, and polyphenylene ether. Thermosetting resins include, but are not limited to, epoxy resin, polyester resin, vinyl ester, bismaleimide, thermosetting polyimide, and cyanate ester. More preferably, the resin is selected from one or more of polyimide resin, epoxy resin, cyanate ester resin, phenolic resin, and bismaleimide resin.
[0018] Preferably, in step 1), the coating treatment method includes: heating the resin to obtain a molten resin, and then coating it to obtain the resin film.
[0019] Preferably, in step 2), the polyimide fiber has a tensile strength ≥ 2.5 GPa, a modulus ≥ 90 GPa, a glass transition temperature ≥ 320℃, and a thermal decomposition temperature ≥ 550℃; and / or
[0020] The polyimide fiber is a long polyimide fiber and / or a continuous polyimide fabric.
[0021] Preferably, in step 2), polyimide fiber bundles are obtained by spinning and splitting the fiber bundles; then, wet polyimide fiber bundles are obtained by sizing, wherein the sizing agent used in the sizing is a water-soluble sizing agent.
[0022] More preferably, in step 2), the main functional group in the sizing agent is one or more selected from epoxy groups, cyanate groups, isocyanate groups, polyurethane groups, phenolic groups, and bismaleimide groups.
[0023] Preferably, the flattening process involves the wet polyimide fiber bundles after sizing being pushed up and down by flattening rollers to achieve parallel sliding, and finally entering a hot oven in a flat state for drying.
[0024] Preferably, in step 2), the drying temperature of the hot oven is 120-160°C; and / or
[0025] In the fiber bundle, the gap between two teeth is 2-8mm, so that 1-3 fibers (e.g., 1, 2 or 3) can be laid flat between the two teeth.
[0026] In this invention, the process of flattening is preceded by sizing. Therefore, flattening mainly relies on the properties of the sizing agent (which not only acts as a flattening agent but also improves the surface activity of the fiber, and the drying process can achieve shaping) and the squeezing action of the pressure roller. In contrast, even if the prepreg preparation method in the prior art involves a flattening process, it mainly relies on air blowing to achieve flattening.
[0027] Preferably, in step 3), the conditions for the hot rolling process include: a temperature of 60-400℃ and a pressure of 0.5-4MPa; preferably, the conditions for the hot rolling process include: a temperature of 80-350℃ and a pressure of 0.5-2MPa; and / or
[0028] The amount of polyimide fiber used is such that the resin content in the prepared prepreg is 20-60% by mass percentage.
[0029] According to another object of the present invention, a second aspect of the present invention provides an ultralight polyimide prepreg prepared by the method described in the present invention, having a unit area mass ≤80 g / m². 2 The layer shear strength is 60-80 MPa.
[0030] According to another object of the present invention, a third aspect of the present invention provides a composite material comprising the ultralight polyimide prepreg described in the present invention.
[0031] By using the above technical solution, compared with the prior art, the present invention can achieve the following beneficial effects:
[0032] (1) It can realize the production of ultra-light polyimide fiber prepreg;
[0033] (2) It can improve the production efficiency and capacity of polyimide fiber prepregs, while reducing production costs;
[0034] (3) It can flatten polyimide fiber bundles;
[0035] (4) It can improve the interfacial properties of polyimide fiber prepreg. Attached Figure Description
[0036] Figure 1 A flow chart illustrating the preparation process of the ultralight polyimide fiber prepreg of the present invention is shown. Detailed Implementation
[0037] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0038] As previously stated, a first aspect of the present invention provides a method for preparing an ultralight polyimide prepreg, comprising the following steps:
[0039] 1) The resin is coated to obtain a resin film;
[0040] 2) The polyimide fibers are processed sequentially as follows: unwinding, sizing, flattening, and drying;
[0041] 3) The polyimide fiber obtained in step 2) is combined with the resin film obtained in step 1) by hot pressing and rolling to obtain polyimide prepreg.
[0042] It should be noted that in this invention, ultralight polyimide prepreg refers to polyimide prepreg with a unit area mass ≤ 80 g / m². 2 Resin content refers to the mass of resin in a single-sided prepreg divided by the mass of the prepreg.
[0043] In this invention, the "resin film" refers to a thin film with certain adhesive properties obtained after resin has undergone processing. According to this invention, the resin can be extruded or coated to form a film.
[0044] According to the present invention, the resin is a thermoplastic or thermosetting resin, and may be selected from any one or more of polyimide resin, epoxy resin, cyanate ester resin, phenolic resin, and bismaleimide resin, but is not limited thereto.
[0045] In this invention, the thermoplastic or thermosetting resin can be obtained by polymerizing dianhydride and diamine.
[0046] In this invention, preferably, the dianhydride is selected from at least one of pyromellitic dianhydride (PMDA), 2,3,3”,4”-biphenyltetracarboxylic dianhydride (α-BPDA), 3,3',4,4'-biphenyltetracarboxylic dianhydride (s-BPDA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenyl ether tetracarboxylic dianhydride (ODPA), and fluorinated dianhydride (TFDA); the diamine is selected from at least one of m-phenylenediamine (s-PDA), p-phenylenediamine (p-PDA), 1,3-bis(4-aminophenoxy)benzene (TPER), 4,4'-diaminodiphenyl ether (ODA), 3,4'-diaminodiphenyl ether (3,4'-ODA), and fluorinated diamine (such as TFDB), preferably a combination of 1,3-bis(4-aminophenoxy)benzene (TPER) and 4,4'-diaminodiphenyl ether (ODA).
[0047] According to the present invention, the thickness of the resin film prepared by the processing can vary within a wide range, and those skilled in the art can make reasonable adjustments according to experimental conditions. In the present invention, preferably, the processing results in a resin film thickness of 50-280 μm, more preferably 70-180 μm, and even more preferably 75-100 μm. At such a thickness, the resin film can better bond and form with the polyimide fibers, obtaining a polyimide prepreg with higher mechanical properties.
[0048] According to the present invention, the polyimide fiber is a polyimide fiber that can be used as a reinforcement in thermoplastic polyimide resin. The polyimide fiber can be selected from a wide range. Preferably, the polyimide fiber used has a tensile strength ≥2.5GPa, a modulus ≥90GPa, a glass transition temperature ≥320℃, and a thermal decomposition temperature ≥550℃.
[0049] To ensure good processing performance and the high-temperature resistance and low dielectric properties of the prepared prepreg used as a composite material, preferably, the polyimide fibers used have a tensile strength of 2.8-4.5 GPa, a modulus of 100-150 GPa, a glass transition temperature of 350-400℃, and a thermal decomposition temperature of 580-630℃. More preferably, the polyimide fibers meeting the above conditions can be long polyimide fibers and / or continuous polyimide fabrics. These polyimide fibers are all conventional raw materials in the art and can be commercially available, for example, long polyimide fibers of grade S35 and continuous polyimide fabrics of grade W-200 (area density 200 g / m²) purchased from Jiangsu Xiannuo New Material Technology Co., Ltd. 2 Radial force > 1600 N / cm.
[0050] According to a preferred embodiment, when the polyimide fiber is a polyimide long fiber and / or a polyimide continuous fabric, since the 0° layup of the polyimide long fiber has better mechanical properties, the polyimide continuous fabric can withstand the same force in the 0° and 90° directions, thereby enabling it to better bond with the resin film under hot pressing conditions, and further producing a composite material with excellent performance.
[0051] According to the present invention, in step 2), compared with the prior art, the prepreg preparation process of the present invention adds sizing and yarn spreading processes, see [link to relevant documentation]. Figure 1 The preparation process flow chart includes processes such as fiber feeding, fiber bundle toothing, sizing, flattening, drying, and film lamination.
[0052] The purpose of sizing is not only to enhance the interfacial bonding force of the fiber surface and eliminate static electricity, but more importantly, to facilitate the flattening of polyimide fiber bundles. This sizing agent has a certain lubricating effect in the solvent, but it has a certain viscosity in the dry state and is rich in N and O polar functional groups, which increases the polarity of the fiber surface.
[0053] Preferably, the sizing agent used in this invention is a water-soluble sizing agent, more preferably a compound of one or more main functional groups selected from epoxy groups, cyanate groups, isocyanate groups, polyurethane groups, phenolic groups, and bismaleimide groups. For example, the main functional group is a compound of epoxy groups and cyanate groups, or a compound of epoxy groups and isocyanate groups. Further preferably, the sizing agent does not contain a benzene ring, and even more preferably, the raw materials for preparing the water-soluble sizing agent include TDE85 epoxy sizing agent.
[0054] It should be noted that the water-soluble sizing agent used in this invention can be selected from water-soluble sizing agents disclosed in the prior art, and can be prepared using conventional methods in the art, as long as the main functional group meets the above conditions.
[0055] In this invention, the flattening method involves first sizing the polyimide fibers, and then, under the action of tension and special sizing liquid, the wet polyimide sized fiber bundles are pushed up and down by flattening rollers to achieve parallel sliding, and finally enter the drying oven in a flat state to achieve drying, which also shapes the flat state of the fiber bundles.
[0056] According to the present invention, in order to further improve the high temperature resistance and low dielectric properties of the prepared prepreg used as a composite material, preferably, in step 3), the amount of polyimide fiber is such that the content of polyimide fiber in the prepared prepreg is 50-90% by weight, preferably 60-70% by weight.
[0057] According to the present invention, the conditions for hot rolling processing depend on the type of resin used. Preferably, in step 3), the conditions for hot rolling processing include a temperature of 60-400°C and a pressure of 0.5-4 MPa. This allows the polyimide fibers to be more uniformly dispersed in the resin film, which is beneficial for obtaining high-performance composite materials.
[0058] Specifically, the hot pressing process can be performed by contacting the resin film with polyimide fibers under the above conditions, and then heating and pressing them with a roller press to make the resin and reinforcing fibers completely composite.
[0059] In a preferred embodiment of the present invention, the preparation method of the ultralight polyimide fiber prepreg adopts a two-step hot-melt method. First, a thermoplastic or thermosetting resin is used for coating, followed by a lamination process. The polyimide fiber sequentially undergoes processes such as unwinding, fiber bundle splitting, sizing, flattening, drying, and lamination with the adhesive film. Splitting involves each fiber bundle passing through one tooth (i.e., between two teeth), with a gap between each tooth (e.g., between two teeth) of, for example, 3.2 mm, facilitating the even laying of 2-3 fibers between each tooth and preventing entanglement and twisting during fiber movement. The sizing agent is a water-soluble sizing agent, environmentally friendly and pollution-free, with the main functional group being a synthesis of epoxy groups and cyanate ester groups, which facilitates improved interfacial bonding strength with the epoxy resin. Under the premise of the sizing agent moistening and lubricating the fiber, the sized fiber bundle is evenly distributed on the flattening roller by the action of the extrusion roller and the flattening roller. After being flattened, the fibers are dried in a hot oven, at which point they become sheet-like and are then fed into a laminating machine to be laminated with an adhesive film.
[0060] A second aspect of the present invention provides an ultralight polyimide prepreg prepared by the method described herein.
[0061] According to the present invention, the ultralight polyimide prepreg prepared by the method described herein is not easily deteriorated, can well meet the requirements of long-term storage and transportation, and has a unit area mass ≤80g / m². 2It has a shear strength of 60-80 MPa, while also possessing ultra-lightweight properties and good interfacial performance. The preferred mass per unit area is ≤70 g / m². 2 More preferably ≤60g / m 2 Further optimization is needed for ≤50g / m 2 Further optimization is preferred for ≤40g / m 2 .
[0062] A third aspect of the present invention provides a composite material comprising the polyimide prepreg described herein.
[0063] According to the present invention, the composite material can be prepared using conventional methods in the art. For example, the polyimide prepreg described in the present invention can be hot-pressed. The hot-pressing conditions can be 2-6 MPa pressure, 100-400°C, and held for 1-4 hours to obtain the composite material.
[0064] The present invention will be described in detail below through embodiments.
[0065] It should be noted that in the following examples, the polyimide fiber used is a high-strength polyimide fiber produced by Jiangsu Xiannuo New Material Technology Co., Ltd., model S35-0.5K / 500D (tensile strength 3.5GPa, modulus 130GPa, glass transition temperature 350℃, thermal decomposition temperature 590℃). The layer shear strength was measured according to ASTM D2344.
[0066] Examples 1-3 illustrate the preparation of ultralight polyimide prepreg. The equipment used in the examples is described in [reference needed]. Figure 1 , Figure 1 A flow chart illustrating the preparation process of the ultralight polyimide fiber prepreg of the present invention is shown.
[0067] Furthermore, the sizing agents used in the examples and comparative examples are all water-soluble sizing agents, which are environmentally friendly and pollution-free. Specifically, the sizing agent for the synthesis of epoxy groups and cyanate ester groups as the main functional group was prepared using TDE85 epoxy resin (Tianjin Jingdong Chemical Composite Materials Co., Ltd.) and bisphenol F cyanate ester (Yangzhou Tianqi New Materials Co., Ltd.) as raw materials; the sizing agent for the synthesis of E51 type epoxy groups and bisphenol F type cyanate ester groups was prepared using E51 type epoxy resin (Jinan Qingtian Chemical Technology Co., Ltd.) and bisphenol F type cyanate ester (Yangzhou Tianqi New Materials Co., Ltd.) as raw materials.
[0068] The specific preparation method refers to the method described in Example 1 of patent application CN201711442951.4, which is as follows: epoxy resin and cyanate ester resin (or isocyanate ester resin) are mixed evenly at 50°C with a molar ratio of 1:0.8, and then mixed evenly with anionic surfactant PAM at a molar ratio of 1:0.05. Distilled water is added to dilute and the mixture is stirred evenly for 30 minutes to obtain a water-soluble sizing agent.
[0069] Example 1:
[0070] The preparation method for ultralight polyimide fiber prepreg employs a two-step hot-melt method. First, an epoxy resin coating (Tianjin Jingdong Chemical Composite Materials Co., Ltd., epoxy resin TDE85) is used, followed by a lamination process. In the coating process, 35g of epoxy resin is heated to 100℃ to obtain molten epoxy resin. The molten resin is then extruded using a film extruder to obtain a resin film with a thickness of 80μm. In the lamination process, the fibers sequentially undergo unwinding, fiber bundle splitting, sizing, flattening, drying, and lamination with the film. The splitting process involves each fiber bundle passing through one tooth, with a 3.2mm gap between each tooth, facilitating the flattening of a single fiber between teeth and preventing entanglement and twisting during fiber transport. The sizing agent is a water-soluble, environmentally friendly, and pollution-free agent. Its main functional group is a composite of epoxy groups and cyanate ester groups, which facilitates improved interfacial bonding strength with the epoxy resin. With the sizing agent moistening and lubricating the fibers, the sized fibers are evenly distributed on the flattening rollers by the action of the extrusion rollers and the flattening rollers. The flattened fibers are then dried in a 150℃ oven, at which point they become sheet-like and enter the laminating machine to be laminated with the adhesive film. The prepreg prepared under these conditions has a basis weight of 40 g / m³. 2 The resin mass fraction in the prepreg is 40%, and the interlaminar shear strength of the prepared composite material is 65 MPa.
[0071] Example 2:
[0072] The preparation method for ultralight polyimide fiber prepreg employs a two-step hot-melt method. First, an epoxy resin coating (Tianjin Jingdong Chemical Composite Materials Co., Ltd., epoxy resin TDE85) is used, followed by a lamination process. In the coating process, 35g of epoxy resin is heated to 100℃ to obtain molten epoxy resin. The molten resin is then extruded using a film extruder to obtain a resin film with a thickness of 80μm. In the lamination process, the fibers sequentially undergo unwinding, fiber bundle splitting, sizing, flattening, drying, and lamination with the film. The splitting process involves each fiber bundle passing through one tooth, with a 6mm gap between each tooth, facilitating the flat laying of one fiber between each tooth and preventing entanglement and twisting during fiber transport. The sizing agent is a water-soluble, environmentally friendly, and pollution-free agent. Its main functional group is a synthesis of epoxy groups and cyanate ester groups, which facilitates improved interfacial bonding strength with the epoxy resin. With the sizing agent moistening and lubricating the fibers, the sized fibers are evenly distributed on the flattening rollers by the action of the extrusion rollers and the flattening rollers. The flattened fibers are then dried in a 150℃ oven, at which point they become sheet-like and enter the laminating machine to be laminated with the adhesive film. The prepreg prepared under these conditions has a basis weight of 30 g / m³. 2 The resin mass fraction in the prepreg is 40%, and the interlaminar shear strength of the prepared composite material is 70 MPa.
[0073] Example 3:
[0074] The preparation method for ultralight polyimide fiber prepreg employs a two-step hot-melt method. First, a cyanate ester resin (bisphenol F type cyanate ester resin from Yangzhou Tianqi New Material Co., Ltd.) is used for coating, followed by a lamination process. In the coating process, 35g of cyanate ester resin is heated to 100℃ to obtain molten cyanate ester resin. The molten resin is then extruded using a film extruder to obtain a resin film with a thickness of 80μm. In the lamination process, the fibers sequentially undergo unwinding, fiber bundle splitting, sizing, flattening, drying, and lamination with the film. The splitting process involves each fiber bundle passing through one tooth, with a 6mm gap between each tooth, facilitating the flat laying of one fiber between each tooth and preventing entanglement and twisting during fiber transport. The sizing agent is a water-soluble, environmentally friendly, and pollution-free sizing agent. Its main functional group is a synthesis of epoxy groups and isocyanate groups, which facilitates improved interfacial bonding strength with the epoxy resin. With the sizing agent moistening and lubricating the fibers, the sized fibers are evenly distributed on the flattening rollers by the action of the extrusion rollers and the flattening rollers. The flattened fibers are then dried in a 130℃ oven, at which point they become sheet-like and enter the laminating machine to be laminated with the adhesive film. The prepreg prepared under these conditions has a basis weight of 30 g / m³. 2 The resin mass fraction in the prepreg is 40%, and the interlaminar shear strength of the prepared composite material is 62 MPa.
[0075] Comparative Example 1:
[0076] Comparative Example 1 differs from Example 1 in that it does not include the flattening process.
[0077] The preparation method for ultralight polyimide fiber prepreg employs a two-step hot-melt method. First, an epoxy resin coating (Tianjin Jingdong Chemical Composite Materials Co., Ltd., epoxy resin TDE85) is used, followed by a lamination process. In the coating process, 35g of epoxy resin is heated to 100℃ to obtain molten epoxy resin. The molten resin is then extruded using a film extruder to obtain a resin film with a thickness of 80μm. In the lamination process, the fibers sequentially undergo unwinding, fiber bundle splitting, sizing, drying, and lamination with the film. The splitting process involves each fiber bundle passing through one tooth, with a 3.2mm gap between each tooth, facilitating the flat laying of a single fiber between each tooth and preventing entanglement and twisting during fiber transport. The sizing agent is a water-soluble, environmentally friendly, and pollution-free agent. Its main functional group is a synthesis of epoxy groups and cyanate ester groups, which facilitates improved interfacial bonding strength with the epoxy resin. After sizing the fibers with a sizing agent, they are dried in a hot oven at 150℃, at which point the fibers are in bundle form. They are then fed into a laminating machine to be laminated with the adhesive film. The prepreg prepared under these conditions has a basis weight of 100 g / m². 2 The resin mass fraction in the prepreg is 40%, and the interlaminar shear strength of the prepared composite material is 60 MPa.
[0078] Comparative Example 2:
[0079] Comparative Example 2 differs from Example 1 in that it does not include the sizing process.
[0080] The preparation method for ultralight polyimide fiber prepreg employs a two-step hot-melt method. First, epoxy resin (Tianjin Jingdong Chemical Composite Materials Co., Ltd., epoxy resin TDE85) is used for coating, followed by a lamination process. In the coating process, 35g of epoxy resin is heated to 100℃ to obtain molten epoxy resin. The molten resin is then extruded using a film extruder to obtain a resin film with a thickness of 80μm. In the lamination process, the fibers sequentially undergo unwinding, fiber bundle splitting, flattening, and lamination with the film. In the splitting process, each fiber bundle passes through one tooth, with a 3.2mm gap between each tooth, facilitating flattening of each fiber and preventing entanglement and twisting during fiber transport. The fibers are then evenly distributed on the flattening roller by the extrusion and flattening rollers, resulting in a flattened bundle shape. This bundle then enters the laminating machine for lamination with the film. The prepreg prepared under these conditions has a basis weight of 80g / m³. 2 The resin mass fraction in the prepreg is 40%, and the interlaminar shear strength of the prepared composite material is 56 MPa.
[0081] Comparative Example 3:
[0082] Comparative Example 3 differs from Example 1 in that it does not include the sizing and flattening processes.
[0083] The preparation method for ultralight polyimide fiber prepreg employs a two-step hot-melt method. First, epoxy resin (Tianjin Jingdong Chemical Composite Materials Co., Ltd., epoxy resin TDE85) is used for coating, followed by a lamination process. In the coating process, 35g of epoxy resin is heated to 100℃ to obtain molten epoxy resin. The molten resin is then extruded using a film extruder to obtain a resin film with a thickness of 80μm. In the lamination process, the fibers sequentially undergo processes such as fiber feeding, fiber bundle splitting, and lamination with the film. The splitting process involves each fiber bundle passing through one tooth, with a 3.2mm gap between each tooth to facilitate even fiber placement and prevent entanglement and twisting during fiber transport. At this point, the fibers enter the laminating machine in bundle form to be laminated with the film. The prepreg prepared under these conditions has a basis weight of 105g / m³. 2 The resin mass fraction in the prepreg is 40%, and the interlaminar shear strength of the prepared composite material is 51 MPa.
[0084] Comparative Example 4:
[0085] The difference between Comparative Example 4 and Example 1 is that the sizing agent formulation was changed. The sizing agent used in Example 1 did not contain a benzene ring, while the sizing agent used in Comparative Example 4 contained a benzene ring.
[0086] The preparation method for ultralight polyimide fiber prepreg employs a two-step hot-melt method. First, epoxy resin (Tianjin Jingdong Chemical Composite Materials Co., Ltd., epoxy resin TDE85) is used for coating, followed by the lamination process. In the coating process, 35g of epoxy resin is heated to 100℃ to obtain molten epoxy resin. The molten resin is then extruded using a film extruder to obtain a resin film with a thickness of 80μm. In the lamination process, the fibers sequentially undergo unwinding, fiber bundle splitting, sizing, flattening, drying, and lamination with the film. The splitting process involves each fiber bundle passing through one tooth, with a 3.2mm gap between each tooth, facilitating the flattening of a single fiber between each tooth and preventing entanglement and twisting during fiber transport. The sizing agent is a water-soluble, environmentally friendly, and pollution-free sizing agent. Its main functional group is a synthesis of E51 type epoxy groups and bisphenol F type cyanate groups, which facilitates improved interfacial bonding strength with the epoxy resin. With the sizing agent moistening and lubricating the fibers, the sized fibers are evenly distributed on the flattening rollers by the action of the extrusion rollers and the flattening rollers. The flattened fibers are then dried in a 150℃ oven, at which point they become sheet-like and enter the laminating machine to be laminated with the adhesive film. The prepreg prepared under these conditions has a basis weight of 43 g / m³. 2 The resin mass fraction in the prepreg is 40%, and the interlaminar shear strength of the prepared composite material is 62 MPa.
[0087] The experimental results of Examples 1-3 and Comparative Examples 1-4 are summarized in Table 1 below. As can be seen from Table 1, Examples 1-3 can prepare ultralight prepregs with a basis weight (i.e., mass per unit area) of up to 40 g / m². 2 Furthermore, this prepreg exhibits high interlaminar shear strength. In contrast, Comparative Examples 1 and 3 failed to produce ultralight prepregs, and while the prepreg in Comparative Example 2 was relatively lightweight, its interlaminar shear strength was low. Additionally, although Comparative Example 4 could produce an ultralight prepreg, the fiber width after spreading was smaller than that of Example 1, and its interlaminar shear strength was weaker than that of Example 1.
[0088] Table 1
[0089]
[0090]
[0091] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Obviously, those skilled in the art can make various modifications and variations to the present invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of the present invention and their equivalents, the present invention also intends to include these modifications and variations.
Claims
1. A method for preparing an ultralight polyimide prepreg, characterized in that, Includes the following steps: 1) The resin is coated to obtain a resin film; 2) The polyimide fibers are processed sequentially as follows: unwinding, sizing, flattening, and drying; 3) The polyimide fiber treated in step 2) is combined with the resin film obtained in step 1) by hot rolling to obtain a unit area mass ≤80g / m². 2 Ultralight polyimide prepreg; In step 2), the polyimide fiber has a tensile strength ≥2.5GPa, a modulus ≥90GPa, a glass transition temperature ≥320℃, a thermal decomposition temperature ≥550℃, and the polyimide fiber is a long polyimide fiber. In step 2), polyimide fiber bundles are obtained by feeding and separating the fiber bundles; then, wet polyimide fiber bundles are obtained by sizing, wherein the sizing agent used in the sizing process is a water-soluble sizing agent; In step 2), the flattening process involves the wet polyimide fiber bundles after sizing being pressed up and down by flattening rollers to achieve parallel sliding, and finally entering the hot oven in a flat state for drying; the main functional group in the sizing agent is one or more selected from epoxy groups, cyanate groups, isocyanate groups, polyurethane groups, phenolic groups, and bismaleimide groups. In step 2), the gap between two teeth in the fiber bundle is 2-8mm, so that 1-3 fibers are laid flat between the two teeth; In step 3), the conditions for hot rolling treatment include: temperature of 60-400℃ and pressure of 0.5-4MPa; the conditions for hot rolling treatment include: temperature of 80-350℃ and pressure of 0.5-2MPa; the amount of polyimide fiber used is such that the resin content in the prepared prepreg is 20-60% by mass.
2. The method according to claim 1, wherein, In step 1), the resin is a thermoplastic resin or a thermosetting resin, and is selected from one or more of polyimide resin, epoxy resin, cyanate ester resin, phenolic resin, and bismaleimide resin.
3. The method according to claim 1 or 2, wherein, In step 1), the coating treatment method includes: heating the resin to obtain a molten resin, and then coating it to obtain the resin film.
4. The method according to claim 1, wherein, In step 2), the drying temperature of the hot oven is 120-160℃.
5. An ultralight polyimide prepreg, prepared by the method according to any one of claims 1 to 4, having a unit area mass ≤ 80 g / m². 2 The layer shear strength is 60-80 MPa.
6. A composite material comprising the ultralight polyimide prepreg of claim 5.
Citation Information
Patent Citations
Water soluble epoxy resin sizing agent for aramid fiber
CN108071018A
Polyimide fiber prepreg and preparation method and application thereof
CN104130548A
Polyimide prepreg and preparation method thereof, and composite material
CN112239554A